Experimental Evaluations of ESF Methods For Neutron Radiographic Image Analysis - Butler, Michael Paul (My University, 1980)
Some experiments designed to test the validity of the edge-spread function (ESF) model for neutron radiographic image formation are described; in addition the experiments are meant to illustrate the application of ESF methods to two areas of practical concern. First, the prediction of optical density curves for specified material and geometric configurations is considered; then, the use of ESF methods in dimensioning irradiated reactor fuel elements is examined. Overall, the results indicate that within the framework of assumptions which ESF theory is based upon, the correlation between theory and experiment is excellent. The results also suggest that in situations which deviate from the theoretical ideal, the ESF method may serve as a good first approximation to more complex models.
Keywords: edge-spread function, ESF, neutron radiographic image fomration, optical density curves, geometric configurations, irradiated reactor fuel elements